Social outlines of the English «campus novel»: historical revision of the subgenre - Дроздовський, Дмитро Ігорович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
Campus novel or academic fiction is a specific genre that has gained worldwide readership. Campuses spread throughout the world provide rich productive raw material for fiction. The trend of campus novels started back a century ago and mainly in the UK.The paper refers to the diachronic transformations that took place in the history of English literature of the twentieth century with such a novelistic subgenre as «campus novel». The key issues related to this subgenre have been outlined taking into account the novels written by Dorothy Sayers, Evelyn Waugh, Charles Percy Snow, John Wain, and Kazuo Ishiguro. The plot specifics of the novels have been spotlighted in the paper. It is also noted that the «campus novel» in the twentieth century has included remarkable elements of social or socio-psychological novel. Philosophical and social parameters of the subgenre have been discussed taking into account the factors that determine the memory of the genre.Campus novels are also called academic novels since these novels focus on the academy. Academy is a place that attracts most people because of its imaginary idealistic notions. It is in fact thought of as a paradise of learning where the inmates dedicate themselves to lofty pursuits. These notions juxtaposed with reality provide a rich source for parody, satire and irony, since some of the people inside it struggle between reality and intellectual pretensions. The strategies of satire and parody have been explained in the paper in English novels of the twentieth century. Academic novels are interesting since they exploit the tension between idealism and corruption. Janice Rossen, a commended campus novel critic who is cited in the paper, points out in her book, The University in Modern Fiction that the primary issue that these novels engage is the interplay between fiction and fact.The Oxford Companion to Twentieth-Century Literature in English (1996) elaborates on Campus Fiction as follows: campus fiction is a term describing a particular genre of novels, usually comic or satirical, which have a university setting and academics as principal characters. The persisting scholarly interest in campus novels was also proved by the 2007 publication of The Academic Novel: New and Classical Essays, a collection edited by Merritt Moseley. The editor’s introduction summarizes the development and reception of the genre up to the early twenty-first century. Moseley argues that most academic novels are comic which does not necessarily make them satirical and concludes that the high incidence of comedy, ranging from the most delicate verbal touches to broad farce, in academic fiction is one of its most valuable and welcomes traits. However, in this paper, the author provides a new outlook on the campus novel spotlighting its social patterns and analyzing this subgenre as an example of confrontation between stereotypical views on humanities and sciences.